New media and hate speech: A study of university students in Jordan - Mokhtar Elareshi, Faisal al Serhan, (Opción, 2020)
Many people are rapidly recognising hate speech as a serious problem, especially via social media sites, resulting in more cyber conflicts between different people. Our study aimed at examining the role of social media in spreading the hate speech among adult university students in Jordan (al Zarqaa University), by determining how social media sites influencing their attitudes, perceptions, feeling safe and how they dealt with information regarding hate speech. Based on a survey data, the study found that most of the respondents were able to identify hate speech in social media sites (77%) and claimed they were exposed to hate speech when using the Internet (83%), especially via Facebook and Twitter.